Clinical Analysis of Intravenous and Oral Sequential Treatment With Voriconazole for Candida Central Nervous System Infection in Six Premature Infants - Zhu, Yingying; Gong, Xiaohui; Li, Zhiling; Wang, Danni; Yan, Chongbing (Frontiers in Pharmacology, 2021)
Objective: To observe the clinical efficacy and safety of intravenous and oral sequential treatment with voriconazole for candida central nervous system (CNS) infection in premature infants. Methods: Retrospectively analyzed the clinical data of 6 premature infants with candida CNS infection admitted to Neonatology in Shanghai Children's Hospital between November 2016 and November 2019. By reviewing the characteristics of voriconazole based on literature, it showed that infants without gastrointestinal dysfunction could be effectively treated by intravenous and oral sequential therapy with voriconazole (both 7mg/kg/dose, every 12 hours). Clinical manifestations, the time required for cerebrospinal fluid (CSF), blood culture, nonspecific infection markers such as platelets and C-reactive protein (CRP) to return normal, and drug-related side effects were observed and recorded in the process of treatment. All data were statistically analyzed by T test and Mann-Whitney U test. Results A total of 6 premature infants were diagnosed with candida CNS infection, 2 cases were diagnosed by positive CSF culture and 4 cases were clinical diagnosed. Blood culture was positive for candida in 5 cases. Among the 6 patients, 4 cases were candida albicans and 2 cases were candida parapsilosis. All the 6 cases were cured. After 3 to 5 days of treatment, symptoms such as lethargy, apnea, feeding intolerance were improved and disappeared; repeated blood culture turned negative in 3 to 7 days; CSF returned to normal in 15±9 days on average. Brain abscess, meningeal inflammation and other infectious lesions were cleared on cranial magnetic resonance imaging (MRI) after treatment. The average total course of voriconazole was 61±29 days, and the average oral treatment was 28±15 days. No candida recurrence was found during the treatment, and no drug-related side effects such as skin rash, liver and kidney function impairment, or visual abnormalities were found. White blood cells, CSF glucose/plasma glucose ratio and protein in CSF were significantly improved after the treatment (p < 0.05). No statistically significant difference was identified in liver and kidney function indexes (p > 0.05). Conclusion Voriconazole is a relatively safe and effective alternative treatment for candida CNS infection in preterm infants. No severe drug-related side effects were detected.